Between Securitisation and Unsafety: A Scaled Analysis of Policing and Structural Vulnerabilisation on the EU Hotspot Samos - Julia Manek; Sophia Popp; Amanda Oiza Bucknor (International Journal for Crime, Justice and Social Democracy, 2025)
The European Union (EU) hotspot system bases itself on securitisation strategies, surrounded by discursive humanitarian promises. In September 2021, the EU opened its first Closed Controlled Access Centre (CCAC) on the Aegean hotspot island of Samos. The EU pledged that the vast securitisation infrastructure, including a police station, would provide safety to asylum seekers. Based on psycho-geographical counter-mappings of forced camp residents (n =  26) and semi-structured interviews with human rights defenders (n  =  5), this article investigates the relations between policing, security, safety and vulnerability on different geographical scales. These scales include the border regime, the hotspot island and the camp. The counter-mappings show how the CCAC renders asylum-seeking people more vulnerable, with their safety being played off against border security. Testimonies of police violence and racism indicate that the intentionality of harm reaches a necropolitical dimension beyond the safety–security nexus. Therefore, we call for reflection on the colonial legacy of border policing and its decolonisation.